1989
DOI: 10.1016/0014-5793(89)80268-6
|View full text |Cite
|
Sign up to set email alerts
|

Prosomes discriminate between mRNA of adenovirus‐infected and uninfected HeLa cells

Abstract: Prosomes are small cytoplasmic RNP complexes associated with repressed mRNA. In in vitro translation, they discriminate between the mRNA of adenovirus‐infected HeLa cells and those of uninfected cells grown under normal conditions. Prosomes as well as their RNA constituents interact much more strongly with poly(A)+ mRNA of infected cells and inhibit their translation in vitro preferentially. A possible role of prosomes in the differential regulation of translation is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…4); (ii) Arrigo et al (35) have demonstrated by RNA sequencing that Drosophila proteasomes are associated with RNA fragments that possess extended adenosine-and uridinerich elements; and (iii) finally, our RNase protection experiments confirmed that proteasomes interact specifically with the 3Ј end of a nondefined number of cytoplasmic RNAs. However, the binding site is not the poly(A) ϩ sequence because proteasome-associated RNA fragments reported so far do not have oligo(A) stretches, and proteasomes associate strongly with TMV-RNA without poly(A) ϩ or with adenovirus mRNAs of which the poly(A) ϩ tail is blocked by oligo(dT) (36). We suspect that proteasomes bind to sequences adjacent or within adenosine-and uridine-rich elements close to poly(A) ϩ and cleave the 3Ј end with the poly(A) ϩ sequences of the corresponding messengers.…”
Section: Discussionmentioning
confidence: 99%
“…4); (ii) Arrigo et al (35) have demonstrated by RNA sequencing that Drosophila proteasomes are associated with RNA fragments that possess extended adenosine-and uridinerich elements; and (iii) finally, our RNase protection experiments confirmed that proteasomes interact specifically with the 3Ј end of a nondefined number of cytoplasmic RNAs. However, the binding site is not the poly(A) ϩ sequence because proteasome-associated RNA fragments reported so far do not have oligo(A) stretches, and proteasomes associate strongly with TMV-RNA without poly(A) ϩ or with adenovirus mRNAs of which the poly(A) ϩ tail is blocked by oligo(dT) (36). We suspect that proteasomes bind to sequences adjacent or within adenosine-and uridine-rich elements close to poly(A) ϩ and cleave the 3Ј end with the poly(A) ϩ sequences of the corresponding messengers.…”
Section: Discussionmentioning
confidence: 99%
“…While no inhibition was observed with globin mRNA and cellular mRNAs of HeLa cells, the translation of TMV-RNA and mRNA isolated from adenovirusinfected HeLa cells was impeded (Horsch et al, 1989). Recent work of our laboratory indicates that proteasome prevents the formation of 80 S initiation complexes but not the early phase of initiation (Homma et al 1994).…”
mentioning
confidence: 90%
“…We and others have demonstrated that proteasomes can interfere with protein synthesis in vitro (Horsch et al, 1989;Lühn et al, 1990). While no inhibition was observed with globin mRNA and cellular mRNAs of HeLa cells, the translation of TMV-RNA and mRNA isolated from adenovirusinfected HeLa cells was impeded (Horsch et al, 1989).…”
mentioning
confidence: 99%
“…Among the 'split factors' are the prosomes, a specific type of RNP of M , 720000, composed of variable sets of small proteins and RNA species that was discovered and characterized over the last years (Schmid et al, 1984;review in Scherrer, 1990). These particles, which have multi-catalytic proteinase activity (Rivett, 1989;Orlowski, 1990), might be involved in mRNA transport and differential pre-translational controls, being split off the mRNA in vivo prior to translation (Grainger and Winkler, 1987) and inhibit initiation of translation in vitro (Kleinschmidt and Buhl, 1987;Horsch et al, 1989). …”
mentioning
confidence: 99%